A new species of Adelophryne Hoogmoed and Lescure 1984 (Amphibia: Anura: Eleutherodactylidae) from the Atlantic rainforest of southern Bahia, Brazil - Lourenço-De-Moraes, Ricardo; Solé, Mirco; Toledo, Luís Felipe (Zootaxa, 2012)
We describe a new species of Adelophryne for the municipalities of Ilhéus, Itacaré and Una, Bahia state, Brazil (typelocality: Reserva Particular do Patrimônio Natural Nova Angélica, municipality of Una, state of Bahia, Brazil,15º15’03.2” S, 39º04’51.0” W, 79 m elevation). This new species is characterized by having small size, anal flap, andpointed tips of all fingers. The advertisement call consists of a single note with average duration of 29.5 ms (22–34 ms).The new species was found under dense leaf litter in primary and disturbed ombrofilous Atlantic rainforest, but in lower abundance in the latter and exclusively in shaded areas.